Manchu and Muscovite / by B.L. Putnam Weale. - Putnam Weale, B. L. (Bertram Lenox), 1877-1930. (Tufts University. Tisch Library., 2015)
1 online resource (xx, 552 pages) : frontispiece, plates (1 folded) map.; "Being letters from Manchuria written during the autumn of 1903; with an historical sketch entitled "Prologue to the crisis", giving a complete account of the Manchurian frontiers from the earliest days and the growth and final meeting of the Russian and Chinese empires in the Amur region."; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.